2001
DOI: 10.1681/asn.v12suppl_1s75
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Detoxification Using the Molecular Adsorbent Recirculating System for Critically Ill Patients with Liver Failure

Abstract: Abstract.Liver failure resulting from different causes and its concomitant complications represent difficult-to-treat conditions with high mortality rates, despite improved therapeutic modalities in intensive care medicine. The accumulation of albumin-bound metabolites that are normally cleared by the liver, such as bilirubin and bile acids, contributes substantially to the development of multiorgan dysfunction in these clinical situations. The molecular adsorbent recirculating system (MARS) represents a cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Acute liver injury (ALI) is a term used to characterize hepatocyte necrosis and significant liver function impairment that occur in a short period without the presence of basic hepatopathy . Cases of severe illness may also have acute liver failure (AHF) or multiple organ dysfunction syndrome . Previous research has demonstrated that inflammation and oxidative stresses, namely the expression of the cyclooxygenase-2 (COX-2) gene and the activation of nuclear factor κB (NF-κB), were the primary causes of ALI .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute liver injury (ALI) is a term used to characterize hepatocyte necrosis and significant liver function impairment that occur in a short period without the presence of basic hepatopathy . Cases of severe illness may also have acute liver failure (AHF) or multiple organ dysfunction syndrome . Previous research has demonstrated that inflammation and oxidative stresses, namely the expression of the cyclooxygenase-2 (COX-2) gene and the activation of nuclear factor κB (NF-κB), were the primary causes of ALI .…”
Section: Introductionmentioning
confidence: 99%
“…1 Cases of severe illness may also have acute liver failure (AHF) or multiple organ dysfunction syndrome. 2 Previous research has demonstrated that inflammation and oxidative stresses, namely the expression of the cyclooxygenase-2 (COX-2) gene and the activation of nuclear factor κB (NF-κB), were the primary causes of ALI. 3 Moreover, the activated NF-κB signal pathway stimulates the release of inflammatory substances from the hepatic salivary cells, such as tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β), and interleukin 6 (IL-6).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The remaining mostly die with the want of a fully functional liver. Given the increasing burden of patients with end-stage liver diseases and the resulting dearth of suitable donor organs, scientists worldwide have been exploring other options, such as extracorporeal temporary liver assist devices [ 22 , 23 , 24 ], tissue engineering approaches, 3D printing and cell-based therapies, to combat liver diseases and most of these have also shown promising results in pre-clinical studies. The fabrication of scaffolds, implantable devices, cell encapsulated hydrogels and 3D printed liver tissues are being investigated under the umbrella of liver tissue engineering [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 The accumulation of metabolites in the human body is thought to be toxic and contributes to many pathological changes in patients with organ failure. 10,11 These toxins could be eliminated by hemodialysis or hemoperfusion; for example, low-density lipoprotein could be removed by adsorbents with sulfonic and cholesterol groups. 12 According to the middle molecule hypothesis, 13 middle-molecular-weight toxins ranging from 500 to 5000 Da are the main toxic substances that accumulate in uremic patients, and middle molecular peptides have been assumed to be one type of major uremic toxin.…”
Section: Introductionmentioning
confidence: 99%